The flipped classroom model for college algebra: effects on student achievement - Overmyer, Gerald Robert, author; Gloeckner, Gene, advisor; Kennedy, Paul, advisor; Rambo-Hernandez, Karen, committee member; Penttila, Tim, committee member (Colorado State University. Libraries, 2014)
In the past few years there has been a substantial rise in the use and interest in a teaching and learning paradigm most commonly known as the flipped classroom. The flipped classroom model encompasses any use of using Internet technology to leverage the learning in a classroom, so that a teacher can spend more time interacting with students instead of lecturing. This is most commonly done by using teacher created videos that students view outside of class time. It is called the flipped class model because the whole classroom/homework paradigm is "flipped". In its simplest terms, what used to be classwork (the lecture) is done at home via teacher-created videos and what used to be homework (assigned problems) is now done in class. Five sections of college algebra where taught using the flipped classroom model. Six sections of college algebra where taught using the traditional method of lecture and homework. This quasi-experimental quantitative research compares sections of college algebra using the flipped classroom methods and the traditional lecture/homework structure and its effect on student achievement as measured through common assessments. In the traditional sections, students spent class time receiving lecture and reviewing homework and exams. Outside class time was spent on traditional homework. In the flipped sections, students viewed short video lectures and submitted basic homework solutions online outside of class time. Students then completed their homework assignments in class with the instructor. Some flipped section instructors also used collaborative group work, inquiry-based learning, and active whole-class discussions. All sections took common assessments for their final exam and completed a pre/post algebra readiness exam. The exam data from the sections were analyzed and compared using regression and ANOVA methods with instructional method, gender, and ACT mathematics scores as independent variables. Final exam scores and pre/post algebra readiness exam scores were the dependent variables. The findings of this research show that there was not a statistically significant difference in the scores of student in the two groups, however students in the flipped sections did score slightly better than student in the traditional sections. Instructors of flipped sections who had previous classroom experience with inquiry-based and cooperative learning methods had sections with statistically significant higher common final exam scores. The results are followed by implications for teaching and recommendations for practice and further research.
Keywords: achievement; algebra; college; flipped; pedagogy; video